Oxymoron Is An Artistic Tool - Abdumalik Saminov (Zien Journals, 2023)
This article discusses the distinctive features of the oxymoron method, which is formed in the pattern of word combinations and serves to express an unusual concept or idea..
Keywords: oxymoron; unusual connection; syntactic model